Harmonization of Law on Transactions E-Commerce in order to support Indonesia's Economic Development - Sidi Ahyar Wiraguna; Faisal Santiago; Ahmad Redi (International Journal Labs, 2023)
Information and Communication Technology has become a necessity in this day and age, many people in Indonesia have utilized it in their daily lives. The dynamics of the economy cannot be separated from the development and progress of technology, infrastructure, productivity and innovation. Advances in science have an impact on technological progress. Disruptive innovation creates its own market that continues in the digital business sector (E-commerce). The development of technology is also accompanied by the development of ways to convey information in communication so that activities become faster by using the internet with social media applications. This research aims to find out the legal harmonization of e-commerce transactions in order to support Indonesia's economic development, to find out legal harmonization can be a solution in providing legal protection for parties in e-commerce transactions. The research method used is normative research with a legal approach and conceptual approach. The types of data include primary materials and secondary materials. The results of the research are, first, in global electronic exchange cannot be given only by one legal point of view, but by legal instruments, creating fair competition which directly or by implication benefits the meeting in global electronic exchange, second e-commerce transactions greatly benefit from the support of Indonesia's economic development when Indonesian law is harmonized. The state offers alternative regulatory models, such as: First, electronic transaction systems that operate either inside or outside the national jurisdiction of a State.